Asymptomatic bacteriuria in early pregnancy: an analysis - P., MuthuPrabha; S., Ramalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Asymptomatic bacteriuria is defined as greater than 100,000 organisms in the urine of a person who lacks symptoms. The objective of present study was to find out the prevalence of asymptomatic bacteriuria (ASB) in women attending the antenatal OPD in a tertiary care centre and to study the effect of screening and treatment on maternal and fetal outcome. Methods: The study was conducted at OG Department, Tirunelveli Medical College Hospital over a period of ten months from March 2014 to Dec. 2014. Antenatal women at 12-16 weeks were screened by collecting clean catch midstream urine samples and doing routine urine analysis, culture/sensitivity and colony count. Treatment was given to all bacteriaurics with oral cephalexin and for persistent cases with Inj. gentamycin. Repeat culture was done at second and third trimesters. Results: In this study, the incidence of ASB was found to be 10.8%. It was more common among primi gravida (13.98%) and the incidence was found to be high in low socio economic groups (12.4%). In present study E. coli was 88.88%, Klebsiella 7.4% and Staphylococcus aureus 3.7%. Anemia was found in 37.04% of bacteriurics, preeclampsia in 7.4%, preterm delivery in 14.82% and low birth weight in 18.5% of bacteriurics. Conclusions: Treatment of ASB during pregnancy at the first antenatal visit decreases the incidence of preeclampsia, premature delivery, low-birth weight and perinatal mortality.